Üniversite Öğrencilerinde Psikolojik Kırılganlıkla Öznel Zindelik Arasındaki İlişkide Genel Psikolojik Sağlığın Aracı Rolü - Ekşi, Halil; Erök Özkapu, Deniz; Ümmet, Durmuş (Muş Alparslan Üniversitesi, 2019)
Theaim of the study is to carry out the mediating role of general psychologicalhealth in relation between psychological vulnerability and subjective vitalityon university students. For this, relational screening method was used. Thesample of the study consisted of 353 university students (280 female, 73 male;age mean: 21, 57). Personal Information Form, Psychological vulnerability scale, subjective vitality scale and general health scale were applied to gather thedata. Pearson correlation method was used as statistical method to identify therelation between variables. And to carry out the mediation role, HierarchicalRegression Analysis and Sobel Test were used. In the light of findings, it wasseen that there was negative correlation between psychological vulnerability, subjective vitality and negative general health condition of universitystudents. In addition to the model created, it was found that psychologicalhealth had the role of mediator between psychological vulnerability andsubjective vitality. Various solutions were put forward by considering thefindings.

Bu araştırmanın amacı üniversite öğrencilerinde psikolojikkırılganlık ile öznel zindelik arasındaki ilişkide genel psikolojik sağlığınaracı rolünü incelemektedir. Bu amaç çerçevesinde araştırmada ilişkisel taramayöntemi kullanılmıştır. Araştırmanın örneklemini 280’i kadın 73’ü erkek olmaküzere toplam 353 üniversite öğrencisi oluşturmaktadır. Öğrencilerin yaşortalamaları 21.57’dir. Araştırmanın verilerini toplamak amacıyla Kişisel BilgiFormu, Psikolojik Kırılganlık Ölçeği, Öznel Zindelik Ölçeği ve Genel SağlıkÖlçeği kullanılmıştır. İstatiksel yöntem olarak değişkenler arası ilişkileribelirlemek için Pearson Korelasyonu hesaplanmıştır. Aracılık rolünü belirlemekiçin Hiyerarşik Regresyon Analizi ve Sobel Testi’den yararlanılmıştır. Eldeedilen bulgulara bakıldığında; üniversite öğrencilerinin öznel zindelikleri ilehem psikolojik kırılganlıkları hem de genel sağlıkları arasında negatifilişkiler olduğu görülmüştür. Ayrıca kurulan modelde, genel psikolojik sağlığınpsikolojik kırılganlıkla öznel zindelik arasında tam aracı rolü olduğubelirlenmiştir.
The Mediating Role of General Psychological Health in Relation between Psychological Vulnerability and Subjective Vitality on University Students
anemon
Keywords: Psychological vulnerability; Subjective vitality; General psychological health; Mediating role; University students; öznel zindelik; psikolojik kırılganlık; genel psikolojik sağlık; aracılık rolü; üniversite öğrencisi